Analysis of the ketamine binding to total plasma protein from domestic cats - Pereira Motta, Victória Paradela; da Silva, Fernanda Ferreira; Caruso, Ícaro Putinhon [UNESP]; Nunes de Goes, Paulo Roberto; Taffarel, Marilda Onghero; Diniz, Andrea; Vicente Seixas, Flavio Augusto (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2024)
Ketamine is a versatile veterinary, clinical, and hospital drug. Evaluating the binding parameters of ketamine to total plasma proteins from domestic cats provides necessary information in determining the value of the pharmacokinetic parameter named distribution volume, which is used for the consequent prospection of drug concentrations in clinical trials. This work aimed to evaluate the binding rate of ketamine to total plasma proteins, the binding constant, and the binding mode to serum albumin in cats. After approval of the project by CEUA/UEM (protocol 3292020621), a plasma pool from six animals (n=6) was reinforced with ketamine concentrations aiming for ultrafiltration with a 10 kDa cutoff membrane device. The drug levels before and after ultrafiltration were analyzed using the liquid chromatography-mass spectrometry technique (LC-MS/MS). The results were calculated using a Scatchard plot to calculate the binding rate and binding constant to albumin. Docking simulations identified the most likely albumin-binding sites. The ketamine binding rate was 65% when the drug reached a plasma concentration above 300 ng⋅mL-1, and the binding constant (Kb) was 2×106 mol⋅L–1 with a positive Hill coefficient (nH) of 2.3. These results show a good correlation between the physicochemical parameters of the drug with structural evaluation by docking simulations and coherence with the values reported by other methodologies in recent literature. This work brought data on the ketamine-binding behavior in cats, an important parameter for future pharmacokinetic evaluations in the search for better protocols for the clinical use of this drug in veterinary medicine.Keywords: Drug development. Analgesia. Felis catus. Albumin.
Análise da ligação da cetamina às proteínas plasmáticas totais de gatos domésticos
Keywords: Albumin.; Analgesia; Drug development; Felis catus